ZnO nanostructures: Comparative synthetic and characterisation studies - Hasany, Syed Farhan; Hussain, Sajid; Ali, Syed M. Usman; Wafaa, Abdul-Kadhim; Muhammad Amir, . (The Institution of Engineering and Technology, 2020)
Tuneful behaviours of nano sized materials have been considered as challenge among researchers to explore the possibility of engaging in diverse applications. In particular, the zinc oxide (ZnO) nanostructured materials offer effective metallic behaviours to enhance the applications in the fuel oxidation, pigments, nonlinear optics and solar energy conversion. In the presented research, ZnO nanoparticles are successfully synthesised by (sol-gel and sol-gel and precipitation) techniques, respectively. The physicochemical behaviours of ZnO nanocrystals were inspected by x-ray diffraction, Fourier transform infrared, field-emission scanning electron microscopy, thermo-gravimetric analysis, N2 physisorption and NH3 temperature-programmed desorption techniques. The results revealed that Sol-gel method at lower pH produced smaller particle sizes with larger surface area and well-established morphology in shorter time at lower temperature conditions, in comparison to precipitation method with higher pH, time and temperature conditions, showed bigger particles with smaller surface area, respectively.